2005
DOI: 10.1039/b501766a
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the enrichment and fractionation of REEs in a newly discovered REE hyperaccumulator Pronephrium simplex by SEC-ICP-MS and MALDI-TOF/ESI-MS

Abstract: Concentrations of rare earth elements (REEs) were determined in the laminae of 10 species of ferns and their acetone-extractable pigments, as well as their host soil and soil extract, by ICP-MS. A new REE hyperaccumulator, Pronephrium simplex, was discovered which could accumulate REEs up to 1.2 mg g(-1) dry mass under natural growth conditions. Three typical species of ferns chosen were divided into lamina, petiole, stem and root for the study of REE translocation and fractionation. A hyphenated technique, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Plant-based remediation techniques can help reduce high REE concentrations in soils through the use of REE-accumulating plants (Chaney et al 1997;Padmavathiamma and Li 2007;Liu et al 2017). Relatively few plant species accumulating REEs are currently known; however, most of them are ferns (Ichihashi et al 1992;Ozaki et al 1997;Wei et al 2001;Zhang et al 2002;Shan et al 2003;Lai et al 2005Lai et al , 2006Liang et al 2014), which could represent a yet unexplored reservoir of REE accumulators. Therefore, we screened a large panel of 49 fern species, all hardy and ornamental ferns, on a substrate spiked with six REEs (La, Ce, Sm, Gd, Yb and Y).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-based remediation techniques can help reduce high REE concentrations in soils through the use of REE-accumulating plants (Chaney et al 1997;Padmavathiamma and Li 2007;Liu et al 2017). Relatively few plant species accumulating REEs are currently known; however, most of them are ferns (Ichihashi et al 1992;Ozaki et al 1997;Wei et al 2001;Zhang et al 2002;Shan et al 2003;Lai et al 2005Lai et al , 2006Liang et al 2014), which could represent a yet unexplored reservoir of REE accumulators. Therefore, we screened a large panel of 49 fern species, all hardy and ornamental ferns, on a substrate spiked with six REEs (La, Ce, Sm, Gd, Yb and Y).…”
Section: Discussionmentioning
confidence: 99%
“…The two species of fern that have the greatest capacity for REE accumulation are particularly interesting. Pronephrium simplex can accumulate up to 1200 mg kg -1 (Lai et al 2005(Lai et al , 2006, while Dicranopteris dichotoma can contain up to 3300 mg kg -1 (Ozaki et al 1997;Wei et al 2001;Shan et al 2003). It has been suggested that high concentrations of REEs in ferns may help these species adapt better to changing environments (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, 22 plant species have been reported to (hyper)accumulate REEs through field and/or laboratory investigations; these species belong to 11 families and 11 genera, with the greatest numbers being pteridophytes (ferns) (Liu et al 2017), such as Pronephrium simplex (up to 1200 mg kg −1 , Lai et al 2005) and Dicranopteris dichotoma (up to 3358 mg kg −1 , Wang et al 1997). Phytolacca americana is a known manganese hyperaccumulator (Min et al 2007;Xu et al 2009;Pollard et al 2009;Xue et al 2010); but also has REE accumulation abilities (Ichihashi et al 1992;Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(synonym: Dicranopteris linearis) and Pronephrium simplex, are fern species. [137][138][139] In contrast, the two currently known REEs hyperaccumulators outside China are woody species. linearis is available.…”
Section: Rare Earth Elements Hyperaccumulatorsmentioning
confidence: 99%